Finding meaning in forgiveness - Tiara Veronika (Universitas Muhammadiyah Banjarmasin, 2024)
The process of developing an adolescent identity will be successful if parents can act as a “safe place” that allows adolescents to feel more confident in exploring the wider world. Not all adolescents can grasp the significance of parenting. Forgiving is the key to recovering from anger and hatred that arise from neglect of parents. Forgiveness can improve relationships and help adolescent understand the meaning of what happened. In this study, we use one type of qualitative research, namely narrative-biographical. This study used a 21-year-old woman who had a bitter experience of being abandoned by her parents. Forgiveness is shown to late adolescents towards their parents for painful experiences they felt. Individual can replace negative feelings with positive feelings, which can be liberating, beneficial to victims and help the find self-acceptance.